Oral and para-oral lymphomas: a 10-year multi-center retrospective study in Egypt with time series analysis and forecasting to 2030 - Madiha Ashoub; Mona Wali; Nada Noureldin; Khaled Keraa; Eman El Desouky; Marwa Mokbel ElShafei (BMC, 2022)
Abstract Background Little is known about the epidemiology of lymphomas occurring in oral and para-oral sites, especially in developing countries such as Egypt. Hence, the aim of this study was to describe the frequency and time trends of oral and para-oral lymphomas in Cairo governorate from 2010 to 2019, with forecasting to 2030, and to examine relations between age, gender, site and type of lymphoma. Methods Histopathological reports of patients diagnosed with oral and para-oral lymphomas from 2010 to 2019 were retrospectively retrieved from archives of six different centers in Cairo governorate. Data regarding age, gender and site was collected and associations between types of lymphoma and these variables were detected using appropriate statistical methods. The significance level was set at p ≤ 0.05. Time series analysis was used to determine the trend of lymphoma frequency within 10 years of the study and to predict frequency until 2030. Results Lymphomas constituted 2.86% of oral and para-oral lesions. Non-Hodgkin lymphoma was more common than Hodgkin lymphoma. Patients with non-Hodgkin lymphoma showed a higher median age than patients with Hodgkin lymphoma (p = 0.001). Non-Hodgkin lymphoma was more prone to occur intra-orally (p = 0.014). No statistical significance was observed in gender distribution between Hodgkin and non-Hodgkin lymphoma. Even though no specific time trend was observed from 2010 to 2019, forecasting for frequency of lymphomas through 10 years (2020 to 2030) showed a predicted increase. Conclusions The findings of this study were consistent with majority of other studies held in various geographic regions. The study revealed that frequency of oral and para-oral lymphomas in Cairo governorate is expected to rise; hence, oral pathologists should be more clinically suspicious and expect to encounter these lesions more in their practice within the upcoming years.